Effect of newborn's admission to intensive care unit on "quality of life" of mother: an Indian perspective. (3rd July 2019) - Rai, Pooja; Rani, Usha
Abstract: Background: Newborn hospitalized in the neonatal intensive care unit (NICU) raises a mother's risk of reduced health-related quality of life (QoL). We explored the contributors inducing stress among mothers related to NICU. Methodology: One hundred thirty-five mothers, whose newborn has completed 48 hours of NICU stay, were interviewed using parental stress scale: neonatal intensive care unit and SF-36 health survey questionnaire for further assessment. Results: The look and behavior of the baby were predominant contributor to the decreased QoL among mothers ( p = <.001). A moderate negative association between parental stresses related to the NICU environment and their QoL ρ = −.467 was observed. Conclusion: It is required to look back at the interiors of the Intensive Care Unit (ICU), the duration provided for the mother and child's physical bonding, the unnecessary noise of the alarms and the jungle of wires around the baby to optimize the QoL of mothers. The further policy requires focusing on building a relation of the mother and child, especially when a child needs supportive care.